COVID-19 in the West Indies: Trinidad and Tobago Experience - Naraynsingh, Vijay; Harnanan, Dave; Maharaj, Ravi; Naraynsingh, Roshni (Journal of Lumbini Medical College, 2020)
Trinidad and Tobago (T+T) is a small twin-island state in the Caribbean, eight miles off the coast of Venezuela. It has an area of approximately 5431 square kilometres and population of 1.4 million. At the present time, there are 116 coronavirus disease (COVID-19) cases and eight deaths, with no new cases or deaths for the last 21 days (May 17, 2020). Its COVID-19 story is one of the prompts, with early control and great success. There has been no such instance where the health services were stretched or unable to cope. Even before the first case was identified, the T+T Government restricted entry to travelers from China, Japan, Singapore, South Korea and several European countries. The first case of COVID-19 identified in T+T was on March 12, 2020. The patient had returned from Switzerland. The next day, a second positive case was a person who had returned from USA.